The Context of Late Humanism - Elezović, Dalibor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This paper examines, from the historiographical aspect, the context of late humanism, the epoch that marked the time between humanism and the Baroque, with its specific cultural and historical development. This short period is a sort of an intermediate stage in cultural and historical phenomena, thus, still in the first half of the 20th century, scientists defined this period as late humanism. The characteristics of late humanism are different social specificities and a wide range of cultural, art, and educational elements that emerged at the time.